2006
DOI: 10.1063/1.2163913
|View full text |Cite
|
Sign up to set email alerts
|

Flow regime analysis of non-Newtonian duct flows

Abstract: Reoriented duct flows of generalized Newtonian fluids are an idealization of non-Newtonian fluid flow in industrial in-line mixers. Based on scaling analysis and computation we find that non-Newtonian duct flows have several limit behaviors, in the sense that such flows can become ͑nearly͒ independent of one or more of the rheological and dynamical control parameters, simplifying the general flow and mixing problem. These limit flows give several levels of modeling complexity to the full problem of non-Newtoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Previous analysis 18 showed that shear-thinning ͑n͒ and yield ͑ ͒ effects lead to comparable flow fields with progressively more solid-like fluid motion, the more non-Newtonian the fluid. Numerical experiments 27 suggest that the velocity field similarity carries over to the advection fields in HB duct flows and that the primary effect of rheology is to delay onset ͑increase ␤͒ relative to Newtonian fluids.…”
Section: Quantifying Non-newtonian Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous analysis 18 showed that shear-thinning ͑n͒ and yield ͑ ͒ effects lead to comparable flow fields with progressively more solid-like fluid motion, the more non-Newtonian the fluid. Numerical experiments 27 suggest that the velocity field similarity carries over to the advection fields in HB duct flows and that the primary effect of rheology is to delay onset ͑increase ␤͒ relative to Newtonian fluids.…”
Section: Quantifying Non-newtonian Effectsmentioning
confidence: 99%
“…In particular limits of the control parameters non-Newtonian behavior may be dominated by shear-thinning ͑through n͒ or yielding ͑through ͒ only and/or depend on the transverse or axial flow ͑through D͒ only; there are rheological simplifications and dynamical simplifications. 18 For n Ն n min or Յ max the HB rheology simplifies to a Bingham fluid ͑B͒ or power-law fluid ͑P͒, and for n Ն n min ഫ Յ max to a Newtonian fluid ͑N͒. As D → 0, the shear rate becomes a function of only the transverse field ␥ ͑u xy ͒ = ␥ xy ; as D → ϱ, the shear rate becomes a function of only the axial field ␥ ͑u z ͒ = ␥ z .…”
Section: Non-newtonian Effectsmentioning
confidence: 99%
See 3 more Smart Citations